MODERASI KOMPETENSI SUMBER DAYA MANUSIA DALAM PENINGKATAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Yenni, Elfita; Junaedi, Achmad Tavip; Wijaya, Evelyn (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
The purpose of this study was to determine and analyze the influence of accounting understanding, Regional Financial Accounting System, Government Internal Control System, and human resource competence on the quality of Pekanbaru City government financial reports. And to determine and analyze whether human resource competence strengthens the influence of accounting understanding, Regional Financial Accounting System, and Government Internal Control System on the quality of Pekanbaru City government financial reports. The population in this study were Civil Servants in Pekanbaru City. The sampling technique for respondents used was purposive sampling, which is a sampling technique based on certain criteria. The research sample included the financial management sub-section, namely 2 people in each OPD. Data analysis used Moderate Regression Analysis. The results of the study stated that accounting understanding had a negative and significant effect, the Regional Financial Accounting System had a positive and insignificant effect, the Internal Control System had a positive and insignificant effect and HR competence had a positive and significant effect on the quality of financial reports of Regional Government Organizations in Pekanbaru City. Accounting understanding through HR competence had a negative and insignificant effect on the quality of financial reports. The application of the Regional Financial Accounting System through the HR Competence variable had a negative and insignificant effect on the quality of financial reports. Internal Control System through HR Competency variable has a positive but insignificant effect on the quality of financial reports.